Bioinformatics Study on Zaire Ebolavirus (EBOV) Protein for Better Understanding the Vaccine Development - Mundaganur, D.S.; Mundaganur, D.Y.; Kannarath, Ashokan (International Journal of Applied Sciences and Biotechnology, 2014)
Nine, Ebola viruse EBOV (Zaire ebolavirus), proteins are extracted from the NCBI repository and their study was carried out. The physicchemical properties and evolutionary link with other such viruses by homology modeling were carried out. All the proteins show rich in leucine domain an ideal requirement for fast attachment of the virus to the receptor molecule on the host cell surface. The prediction of trans-membrane sequence for the entire glycoprotein component reveals the ability of the virus to enter the host with ease. The lack of adequate homology model for the viral proteins indicates its novel origin and lack of well traceable evolutionary link. We studied the homology based model by using various available tools and find similar approach in all, hence finally concentrated only on one method. The model predicted shows well acceptable region on Ramchandran plot. This discrepancy is only due to the fact that we validate the model to Ramchandran plot and the model predicted were not under the well acceptable ‘e’ value range i.e. >1. Therefore we suggests that vaccine production against this deadly virus should be concentrated on the structure and functions of glycoprotein like low quality secreted glycoprotein (NP_066248), low quality spike glycoprotein(NP_066246)0, small secreted glycoprotein (NP_066247) and RNA dependent RNA polymerase (NP_066251). DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11588Int J Appl Sci Biotechnol, Vol. 2(4): 544-552